Miniature thermoelectric power plant - Moreira, António H. J. (2006)
This paper describes a miniature thermoelectric power plant made with the boiler and the water pump from an old starch iron. It also uses a computer cooling fan, which serves as electric power generator. The boiler vaporizes the water it receives from the water pump. Then, the steam is injected over the turbine of the fan making it twirl. The voltage generated by the fan is enough to lighten a couple of LEDs. A wooden case with a chimney encloses all the referred devices.